Design and Finite Element Analysis of Aircraft Wing using Ribs and Spars - Vinay Kumar. P, I. Rahul Raj, M. Snehith Reddy, N. Siva Prasad (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, project detailed design of trainer aircraft wing structure made by using CATIA. Then stress analysis of the wing structure is carried out to compute the stresses at wing structure. The stresses are estimated by using the finite element approach with the help of ANSYS to find out the safety factor of the structure. In a structure like airframe, a fatigue crack may appear at the location of high tensile stress. Life prediction requires a model for fatigue damage accumulation, constant amplitude S-N (stress life) data for various stress ratios and local stress history at the stress concentration. The response of the wing structure will be evaluated.In this thesis, the trainer aircraft wing structure with skin, spars and ribs is considered for the detailed analysis. The wing structure consists of 15 ribs and two spars with skin. Front spar having „I‟ section and rear spar having „C‟ section. Stress and fatigue analysis of the whole wing section is carried out to compute the stresses and life at spars and ribs due to the applied pressure load.In this project, the mentor aircraft wing with winglets with at different angles (450 and 250) is thinking about for the itemized investigation. Static and fatigue analysis of the entire wing area is done to figure the burdens and life at various winglet points (250 and 450) because of the applying weight load.